Loyalty in the post-pandemic landscape: Unraveling how behavioral intentions shape m-banking loyalty - Ikhlash, Muhammad; Huwaida, Jihan Hana; Asmu'i, Faishal (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2023)
Many activities have switched to online, carrying out remote activities due to the pandemic that has hit worldwide and requires staying home to avoid physical contact with other people. One of the activities carried out to reduce physical contact is transacting online using m-banking. This study aims to empirically test the effect of behavioral intention on use behavior. This study was limited to testing the effect of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit, trust, and security on behavior intention and intention to use behavior in students. This study applied a quantitative approach, and there were 100 respondents. The sampling technique used a purposive sampling method. Data collection was carried out by distributing questionnaires, and then the data was processed using SmartPLS version 4.0 to carry out instrument and hypothesis testing. The results of the study explained that habit and security had a positive influence on behavioral intention, and behavioral intention had a positive influence on use behavior.